Microwaves can kill malaria parasites non-thermally - Coronado, Lorena M.; Stoute, José A.; Nadovich, Christopher T.; Cheng, Jiping; Correa, Ricardo; Chaw, Kevin; González, Guadalupe; Zambrano, Maytee; Gittens, Rolando A.; Agrawal, Dinesh K.; Jemison, William D.; Donado Morcillo, Carlos A.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Malaria, which infected more than 240 million people and killed around six hundred thousand only last year, has reclaimed territory after the SARS-CoV-2 pandemic. Together with parasite resistance and a not-yet-optimal vaccine, the need for new approaches has become critical. While earlier, limited, studies have suggested that malaria parasites are affected by electromagnetic energy, the outcomes of this affectation vary and there has not been a study that looks into the mechanism of action behind these responses. In this study, using microwave energy (MW), conditions in which more than 90% of the parasites are killed, not by a thermal effect but via a MW energy-induced programmed cell death that does not seem to affect mammalian cell lines, were generated. Transmission electron microscopy revealed that exposure to MW leads to destruction of the food vacuole, consistent with the observation of leakage of calcium ions from the vacuole to the cytoplasm. Furthermore, parasites were protected from the effects of MW by calcium channel blockers, calmodulin, and phosphoinositol. As previously reported by our group, direct current electric fields cause the opposite effect, i.e., proliferation of the parasites by means of the same calcium signaling molecules. Evidence that suggests that a Plasmodium falciparum BAX-like (PfBAXL)molecule is key for the inhibitory effect of MW on the pathogen. These findings offer a molecular insight into the elusive interactions of oscillating electromagnetic fields with P. falciparum, prove that they are not related to temperature, and present an alternative technology to combat this devastating disease.